IMPROVING STUDENTS’ ACHIEVEMENT IN SPEAKING THROUGH BRAINSTORMING TECHNIQUE - Defriyanti Ziraluo; Lince Sihombing (Universitas Negeri Medan, 2014)
The objective of this study is to find out whether Brainstorming Technique can improve students’ Achievement in speaking. This study was conducted by using classroom action research. The subject of this research was the second year students of SMA Swasta Katolik Budi Murni 3 Medan. The research was conducted in two cycles. The first cycle was three meetings and the second cycle was two meetings. The instruments for collecting data used speaking test for quantitative data and used diary notes, questionnaires sheet, interview and observation sheet for qualitative data. Based on the speaking test result, the students’ score kept improving in every test. In orientation test, the mean score was 47,8. In the test of cycle 1 the mean score was 59,2 and the mean score in the test of cycle 2 was 70,1. In line with the data, it was found that the Brainstorming technique can improve students’ speaking achievement.